2012
DOI: 10.1108/17410401211249193
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation, learning orientation, and the performance of nonprofit organisations (NPOs)

Abstract: Purpose -Nonprofit organisations (NPOs) are challenged with continuous change, which provides the impetus for adopting organisational change models. The purpose of this paper is to examine the impact of the adoption of market and learning orientations on NPO performance. Design/methodology/approach -The authors draw on extant management literature to theorise the interrelationship between market orientation, learning orientation, and economic and non-economic NPO performance. Using a survey design, the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 85 publications
(237 reference statements)
2
19
0
Order By: Relevance
“…The extant LO literature has revealed a strong positive relationship between LO and organizational‐level outcomes. Some of the studies have focused on the direct effect of LO on organizational performance and found a positive relationship between them (Abdulai Mahmoud and Yusif ; Baker and Sinkula ; Beneke et al. ; Calantone, Cavusgil and Zhao ; Mavondo, Chimhanzi and Stewart ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…The extant LO literature has revealed a strong positive relationship between LO and organizational‐level outcomes. Some of the studies have focused on the direct effect of LO on organizational performance and found a positive relationship between them (Abdulai Mahmoud and Yusif ; Baker and Sinkula ; Beneke et al. ; Calantone, Cavusgil and Zhao ; Mavondo, Chimhanzi and Stewart ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…; Calantone, Cavusgil and Zhao ; Mavondo, Chimhanzi and Stewart ). For example, Abdulai Mahmoud and Yusif () investigated the effect of LO in non‐profit organizations and found that LO was positively related to economic and non‐economic organizational performance – specifically, non‐economic performance was the mediator in the relationship between LO and economic performance. Another important and popular organizational outcome that has been examined in LO research was firm innovation.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, MO involves the use of superior organizational skills in understanding and satisfying customers. It facilitates an organization's ability to anticipate, react to, and capitalise on environmental changes, thus, leading to superior performance (Mahmoud and Yusif 2012). ISSN 2162-4860 2017 Narver and Slater (1990) state that MO has three components.…”
Section: Market Orientationmentioning
confidence: 99%
“…Some researchers also study the effects of learning orientation on organizational performance or new firms' competitive advantage through the mediation effects of knowledge innovation, team trust, product innovation, and knowledge integration (Baba, 2015;Haryanto, Haryono, & Sawitri, 2017;Huang & Li, 2017;Mahmoud & Yusif, 2012;Sikora, Nybakk, & Panwar, 2016;Wu, Tsai, & Tai, 2016).…”
Section: Effects Of Learning Orientation On Dynamic Capabilitymentioning
confidence: 99%